ERROR ANALYSIS OF EFL STUDENTS IN TRANSLATION: A STUDY AT EVEREST ENGLISH COURSE, SURABAYA - Annisa Triana Flyandjono; M. Afifulloh (Smart Edu Center, 2025)
This paper aims to highlight pragmatic failure and to analyze the translation errors made by EFL (English as a Foreign Language) students at Everest English Course, Surabaya. The researcher focuses on the mistakes often occurring in English classes. The method of this study is descriptive qualitative, which focuses on describing student's translation errors. The acquisition uses the theory introduced by (Corder, 1967; Richards, 1971) to identify the types of interlingual or intralingual matters. The research involves 25 randomly selected students of varying ages (male and female) as subjects of this examination. They were given some translation tasks for seven phrases and sentences without looking up the meaning in a dictionary. The most frequent mistake appeared in the phrase